Validação transcultural da versão F38 da Escala Impacto Familiar da Tecnologia Assistiva: Escala para Comunicação Alternativa (FIATS-AAC BR) - Reis, Isabela Irano dos (2025)
It is widely recognized in the literature that a higher level of exposure of children with complex communication difficulties is positively associated with more favorable results in the development of their communication skills. In this sense, the family is extremely relevant in the process of implementing Augmentative and Alternative Communication (AAC). Based on this, the Canadian Family Impact of Assistive Technology Scale for Augmentative and Alternative Communication (FIATS-ACC) has been applied in several countries and aims to investigate the impact of the use of AAC systems on family life. The original scale contains 89 items; with the aim of reducing it and making it possible to use it in situations where the original version would not be feasible, the reduced version of the scale called FIATS-AAC-38 offers a reliable assessment of family and child functioning as perceived by parents in 38 items. Since there is a translated and validated version of the FIATS-AAC-Br for Brazil, this follow-up study aimed to verify the reliability of the translated and reduced version of the scale called FIATS-AAC-Br-38, in order to assess its internal consistency and stability. The methodological and cross-sectional research used as materials the FIATS-AAC-Br scale, the reduced version FIATS-AAC-Br 38 and its components. To assess internal consistency and stability, two applications of the FIATS-AAC-BR-38 scale were carried out with fifteen family members of children with complex communication needs who use AAC systems, with an interval of between ten and fifteen days; and to perform concurrent validity, that is, by comparing the scores obtained between one instrument (FIATS-AAC-Br 38) and another already established (FIATS-AAC BR), 21 family members composed the sample. The participants were selected based on advertising on social networks and contact with professionals in the area. The data were tabulated, and Cronbach's alpha was applied. The nonparametric Wilcoxon test was used to evaluate the test and retest. The results indicated high internal consistency among the items. However, some questions presented negative gross correlations with the total scale, indicating the need to increase the sample size to ensure validation through confirmatory factor analyses in future studies. It is concluded that the reduced version is suitable for application in the country, and that new statistical analyses can be used to expand the study of its validation. Thus, it is considered that the research achieved its objectives and contributed to the provision of another tool to be used in the process of proposing and monitoring AAC by professionals in Brazil.